IMPLEMENTASI PENDIDIKAN BUDI PEKERTI DISIPLIN DI SEKOLAH DASAR DALAM MENGHADAPI TANTANGAN DALAM PENERAPANNYA - Damayanti, Indah; Nuraini, Joya; Tania Putri, Liana; Fitri Nurdiantiny, Melani; Nabil Muttaqin, Muhammad; Iskandar, Sofyan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the implementation of discipline focused character education in elementary schools and the challenges encountered in its application amid rapid technological and social changes. The purpose of this research is to analyze the forms of discipline, the influencing factors, the obstacles faced by schools, teachers, and students, and to identify effective strategies for strengthening discipline as a fundamental character value. Using a qualitative approach through a systematic literature review, the study analyzes journal articles, books, policy documents, and research reports published within the last ten years. Data were collected through source mapping, thematic categorization, and synthesis to obtain a comprehensive understanding of discipline development in elementary education. The findings indicate that student discipline remains inconsistent, as evidenced by habitual lateness, incomplete assignments, inattentiveness, and failure to follow school rules. These issues arise due to unclear regulations, inconsistent enforcement, weak teacher role modeling, limited parental involvement, and negative peer or media influence. The study explains that such challenges persist because students have not fully internalized discipline and because schools often focus on punitive measures rather than constructive character-building approaches. Therefore, the success of discipline implementation depends on collaborative support between schools, teachers, parents, and the broader community. The study concludes that solutions such as co-constructing classroom rules, habit-building routines, positive teacher modeling, improved classroom management, home school collaboration, and balanced reward and consequence systems significantly enhance students disciplinary behavior. These strategies have a positive impact on creating conducive learning environments, strengthening students responsibility, self-control, and moral awareness, and promoting long-term character development. Ultimately, discipline-centered character education shapes students into competent, ethical, and responsible individuals who are prepared to face future challenges.